Intraosseous xanthoma of the mandible: A multi‐institutional case series with a literature review. (17th September 2019) - de Arruda, José Alcides Almeida; Almeida, Tatiana Fernandes Araújo; Abreu, Lucas Guimarães; do Amaral, Márcio Bruno Figueiredo; Anbinder, Ana Lia; Flores, René Martínez; Agostini, Michelle; Romañach, Mário José; Silva, Tarcília Aparecida; de Andrade, Bruno Augusto Benevenuto; Mesquita, Ricardo Alves
Abstract: Background: The aim of the present study was to report the clinicopathologic, radiographic and immunohistochemical features of five South American cases of intraosseous xanthomas of the mandible and to compare them to those detected in a literature review. Methods: Clinical data were collected from the records of three Oral and Maxillofacial Pathology services in South America and compared with those compiled from a literature review based on a search of three electronic databases (PubMed, Web of Science and Scopus). All cases were evaluated by haematoxylin and eosin staining and immunohistochemistry for CD68 and S‐100. Results: The series comprised four females (80%) and one male (20%) with a mean age of 23.3 ± 10.9 years (range: 13‐45 years). In four cases, there was involvement of the posterior region of the mandible (80%). The lesions presented radiographically as unilocular (60%) radiolucencies with punched‐out margin (80%). All cases predominantly consisted of CD68‐positive and S‐100‐negative xanthomatous cells. No recurrences were observed after curettage, with a median follow‐up of 27 months. Conclusion: Intraosseous xanthoma of the jaws is a rare benign disorder. We report here five additional cases affecting the mandible, for a total of 36 cases of the jaws reported in the literature. Overall, this lesion has predilection for posterior sites of the mandible of asymptomatic young adults.